Chemical fertilization: a short‐term solution for plant productivity?. Issue 5 (27th November 2019) - Molina‐Santiago, Carlos; Matilla, Miguel A.
Abstract : The effect of long‐term chemical fertilization on plant‐microorganisms and microbe‐microbe interactions.